AGAMA DAN PEMBENTUKAN REALITAS DALAM PANDANGAN PETER LUDWIG BERGER - Rudy Harold (Cakrawala Jurnal Penelitian Sosial, 2016)
This paper attempts to peer into the mind of Peter L.Berger in understanding the reality of religion. With the aim to obtain a description of sociological and theoretical fuller on how religion plays a role in the formation and preservation of the human world created for the benefit of the formation itself as being the "unfinished". From the results of the study found that religion is a means of legitimacy to perpetuate the human nomos varied created that can be received from one generation to the next. The authors recognize that the thought of Peter L. Berger is also not spared from the reductionist understandings of the reality of religion, but would not it be reductionist if we can not accept that religion has contributed greatly to the establishment and maintenance of the created world humans in daily life -day which takes place dialectically.Keywords: Lebenswelt, Externalization, Objectification, Internalization, Dialectics, Nomos and Kosmos.